Features of the teaching of medical disciplines in the conditions of war - Boichuk, O.; Lopushniak, Lesia; Dronyk, I.; Sukhonosov, Roman (Сolloquium-journal, 2023)
During a full-scale war, teaching in higher education institutions encounters significant obstacles and modifications due to the conflict's specificity and danger, limited access to educational resources and other restrictions. Military operations limit access to educational institutions, materials, textbooks, supplementary materials, and equipment, which necessitates teachers to be more creative and to adjust their curricula accordingly. It is appropriate and relevant to offer courses in military medicine that include a comprehensive study of human anatomy and other crucial disciplines in higher and pre-higher medical education institutions, to prepare students for working in the front lines. Teaching medical disciplines, such as human anatomy, in times of war poses a very challenging but indispensable task due to the prevailing stressful conditions. Competent teaching of the material along with the development of algorithms and options for action in extreme situations is crucial. Additionally, students should be provided with moral support to manage daily emotional stress effectively. Considering these factors, it is imperative to adapt the curriculum and teacher behaviour during wa rtime for the effective teaching of medicine. This is a crucial element in delivering high-quality medical care and saving lives.
Особливості викладання медичних дисциплин в умовах війни
Keywords: військові дії; викладач; навчання; студент; лікар; military operations; teacher; education; students; doctor